Analisis Pengembalian Modal Pada Usaha Angkringan "Mang Udin" Di Kota "Cikarang" - Eka Radita Putri; Rachma Tryadzanita S; Amelia Manda Putri; Yosi Ragil Cahyono; Fiqih Maria Rabiatul Hariroh (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to analyze the level of return on capital in the "Mang Udin" angkringan business operating in the city of "Berkah". Data was collected through surveys and interviews with business owners as well as analysis of financial documentation. Apart from that, this research also involved direct observation of the operation of the angkringan. The research results show that the initial business capital, operational cost structure, average monthly income and return on capital were obtained. Analysis is also carried out to identify factors that influence return on capital.